Efeitos da intervenção psicoeducativa com enfoque na estimulação cognitva para cuidadores de idosos com doença de Alzheimer - Caparrol, Ana Julia de souza (Universidade Federal de São Carlos, 2021)
Introduction: The increase in elderly people diagnosed with Alzheimer's disease (AD) brings challenges to society, especially to family members, who often become informal caregivers, culminating in a series of biopsychosocial complications. Among them, there is the impairment in cognitive performance, which can directly affect the quality of life of these individuals, establishing the need for support programs. Objective: to evaluate the effects of a psychoeducational home intervention on cognitive performance, anxious symptoms, stress and burden in caregivers of elderly people with AD. To meet the major objective, two studies were designed, with the following objectives: (1) To carry out a systematic review of the literature on psychoeducational interventions with caregivers of elderly people with AD; (2) apply a psychoeducational intervention with a focus on cognitive stimulation and evaluate its effect on cognitive performance, anxiety, stress and the burden of caregivers of elderly people with AD.. Method: The study (1) was configured as a systematic review of scientific production with search in the databases Pubmed, Virtual Health Library, MEDLINE, PsyINFO, Scopus and Cochrane, published until December 2019, in English, Portuguese or Spanish. The search strategy combined the Boolean terms and operators considering the key concepts "caregivers", "elderly", "intervention", "Alzheimer's disease", "cognition", "psychosocial impact", "psychosocial support systems". The study (2) deals with a randomized, controlled and blinded clinical trial, for the application of a psychoeducational intervention focusing on cognitive stimulation in caregivers of elderly people linked to the Home Care Department of a private health operator in the city of São Carlos (SP). Results: (1) Eight articles were analyzed, which showed improved knowledge about AD, in addition to better self-efficacy, resilience and cognitive performance of caregivers. (2) The Intervention Group showed significant improvement in the symptoms of stress (p = 0.027), global cognition (ACER p = 0.003; MMSE p = 0.008) and domains (attention / orientation - p = 0.004; memory - p = 0.017; fluency verbal - p = 0.023). As for the Active Control Group, even if not significant, there was an improvement in verbal fluency that showed in the reevaluation (p = 0.007), perceived stress (p = 0.031) and anxiety symptoms (p = 0.049). Conclusion: (1) Models of psychoeducational interventions for caregivers of elderly people with AD are proposed in different formats and demonstrate positive effects regarding their self-efficacy, resilience and cognitive performance. (2) Home intervention for caregivers is an important tool for improving cognition and stress in caregivers of elderly people with AD, but it does not seem to have the same efficacy for symptoms of overload and anxiety, which highlights the need for specific intervention strategies for this domain.
Effects of psychoeducational intervention with a focus on cognitive stimulation for caregivers of elderly people with Alzheimer's disease
Keywords: Doença de Alzheimer; Idoso; Cognição; Cuidadores; Caregivers; Alzheimer's disease; Aged; Cognition; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PSIQUIATRICA; OUTROS::CIENCIAS; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA